THE CHALLENGES OF MANAGING DIVERSITY IN ORGAZIZATIONS - de jesus, Joandson Santos; da Costa, Elvio Carlos (Revista Interface Tecnológica, 2022)
The present work focuses on the theme of managing diversity and inclusion in the corporate context. Diversity has always been in our midst, but nowadays it has gained more prominence and relevance, since companies have obtained advantages in actions that promote such inclusion and diversity, in addition to providing more engagement with the demands of contemporary society. In this sense, the objective of this study was to know the advantages that diversity actions provide to organizations, in relation to creativity, competitiveness, profitability and visibility in such a globalized world. Methodologically, a bibliographic research was carried out, through a survey in the Scielo and Google Scholar databases. The results obtained are very consistent, and make us reflect on how much we still need to evolve, either as a company or as people, because in addition to standing out in relation to the competition, it was verified that the financial return, especially with regard to billing and profitability, are advantageous for organizational strategies. In view of this, it can be said that investing in diversity brings benefits both to companies and to society in general, since the well-being practiced internally in companies will possibly reflect on people's daily lives.
Keywords: Management; Diversity; Inclusion; Results; Competitiveness